Prevailing Insects And Mite Pests Of Brinjal And Their Natural Enemies At Jashore In Bangladesh (Bangladesh Journal of Agricultural Research, 2023)
Abstract not availableBangladesh J. Agril. Res. 46(1): 117-121, March 2021